The effect of lithium on the progression‐free and overall survival in patients with metastatic differentiated thyroid cancer undergoing radioactive iodine therapy. (13th August 2018) - Luo, Hongxiu; Tobey, Andrew; Auh, Sungyoung; Cochran, Craig; Zemskova, Marina; Reynolds, James; Lima, Cristiane; Burman, Kenneth; Wartofsky, Leonard; Skarulis, Monica; Kebebew, Electron; Klubo‐Gwiezdzinska, Joanna
Summary: Objective: Pretreatment with lithium (Li) is associated with an increased residence time of radioactive iodine (RAI) in differentiated thyroid cancer (DTC) metastases. There are no data translating this observation into long‐term outcomes. The study goal was to compare the efficacy of three methods of preparation for RAI therapy in metastatic DTC—thyroid hormone withdrawal (THW), THW with pretreatment with Li (THW+Li), and recombinant human TSH (rhTSH). Design/Patients/Measurements: We performed a cohort study comparing overall survival (OS) and progression‐free survival (PFS) between the three groups: THW (n = 52), THW+Li (n = 41) and rhTSH (n = 42). Kaplan‐Meier analyses were performed to compare OS and PFS between the groups. Cox proportional hazards regression model with a stepwise variable selection was performed to study the contribution of age, gender, histology, TNM status, a location of distant metastases and RAI dose. Results: During the follow‐up of median 5.1 (IQR = 3.0‐8.1) years, 52% of patients had disease progression and 12.6% died. Although THW+Li group was characterized by the longest OS ( P  = 0.007), only age (HR 1.05, CI 1.01‐1.09, P  = 0.01) and widespread disease (HR 3.8, CI 1.2‐11.8, P  = 0.02) were found to affect OS in a multivariate model. There was no difference in PFS between the groups ( P  = 0.47). Presence of distant metastases limited to the lungs only was associated with longer PFS (PFS HR 0.35, CI 0.20‐0.60, P  = 0.0002). Conclusion: The older age is associated with shorter OS, while disease burden affects OS and PFS in patients with metastatic thyroid cancer. The method of preparation for RAI therapy does not affect the outcome.